Effect of aging on mitochondria and metabolism of bovine granulosa cells - Shuta NAGATA; Kaoru TATEMATSU; Kazuki KANSAKU; Yuki INOUE; Mitsuru KOBAYASHI; Koumei SHIRASUNA; Hisataka IWATA (The Society for Reproduction and Development, 2020)
This study investigated the effect of aging on mitochondria in granulosa cells (GCs) collected from the antral follicles of young and aged cows (25-50 months and over 140 months in age, respectively). When GCs were cultured under 20% O2 for 4 days, mitochondrial DNA copy number (Mt-number), determined by real-time PCR, increased throughout the culture period, and the extent of increase was greater in the GCs of young cows than in those of old cows. In a second experiment, GCs were cultured under 20% O2 for 24 h. Protein levels of TOMM20 and TFAM in GCs were lower in aged cows than in young cows, and the amount of reactive oxygen species and the mitochondrial membrane potential were higher, whereas ATP content and proliferation activity were lower, respectively. Glucose consumption and lactate production were higher in the GCs of aged cows than in those of young cows. When GCs were cultured under 5% or 20% O2 for 24 h, low O2 decreased ATP content and increased glucose consumption in GCs of both age groups compared with high O2; however, low O2 decreased the Mt-number only in the GCs of young cows. In conclusion, we show that aging affects mitochondrial quantity, function, and response to differential O2 tensions in GCs.